PERANCANGAN ULANG TATA LETAK GUDANG PADA CV. ASRI RAYA SIDOARJO - Nevi Anjani (CALYPTRA, 2019)
Abstrak : This research aims to re-design the layout of the CV. Asri Raya, Sidoarjo warehouse to have efficient and effective warehouse layout. Redesigned warehouse layout using Activity Relationship Chart (ARC) method and ABC classification method, by looking at policy analysis, area dimension analysis and item deminsion analysis. This research uses data penjulan for one full year in 2016 and data amount of goods sent by company. The results of this study, shows that the redesign layout of the CV. Asri Raya warehouse based on existing methods and analyzes to make the company more efficient and effective in the taking and laying of goods in the warehouse. Keywords: Warehouse, Layout, Activity Relationship Chart (ARC), ABC Classification